Imbalanced randomization in clinical trials. (3rd April 2020) - Chandereng, Thevaa; Wei, Xiaodan; Chappell, Rick
Abstract : Randomization is a common technique used in clinical trials to eliminate potential bias and confounders in a patient population. Equal allocation to treatment groups is the standard due to its optimal efficiency in many cases. However, in certain scenarios, unequal allocation can improve efficiency. In superiority trials with more than two groups, the optimal randomization is not always a balanced randomization. In noninferiority (NI) trials, additive margin with equal variance is the only instance with balanced randomization. Optimal randomization for NI trials can be far from 1:1 and can greatly improve efficiency, a fact which is commonly overlooked. A tool for sample size calculation for NI trials with additive or multiplicative margin with normal, binomial, or Poisson distribution is available at http://www.statlab.wisc.edu/shiny/SSNI/ .